B2B Website constraints, evaluation, and benefits in small and medium sized enterprises - Lin, Chad; Huang, Y.; Stockdale, R. (National Chung Cheng University, 2008)
The issues of constraints, evaluation, and actual realization of benefits from investments in B2B website have generated a lot of attention in the information systems management literature among researchers and practitioners in recent years. This research builds on a survey that assessed the websites of small businesses in Australia from an owner’s perspective to determine the benefits of the websites from the owners’ perspective. The objective of this paper is to examine the relationships between B2B website adoption constraints, IT investment evaluation, and B2B website benefits. A key contribution of the paper is that B2B website adoption constraints is negatively related to the level of IT investment evaluation which in turn has a positive impact on the realization of B2B website benefits.